(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
The history of genetics, since its origin, has transcended the scientific dimension, interweaving social, cultural, and political contexts. This brief contribution aims both to offer a chronological overview of scientific achievements in the field of genetics, starting from the pivotal work of Mendel and Darwin, and to outline concepts and themes that have emerged over time. It will show how the history of genetics allows us to reflect on some peculiar dynamics of the history of scientific thought, such as the evolution of scientists’ image, its relationship with society, the birth of new forms of cooperation (from the small lab to Big Science), and a constant, intense dialogue among the different social actors. All these elements still strongly characterize genetics today and investigating their historical roots will help us understand their nature and raison d’être.